A Validation Study on eGFR Equations in Chinese Patients With Diabetic or Non-diabetic CKD - Xie, Danshu; Shi, Hao; Xie, Jingyuan; Ding, Ying; Zhang, Wen; Ni, Liyan; Wu, Yifan; Lu, Yimin; Chen, Bing; Wang, Hongrui; Ren, Hong; Wang, Weiming; et al. (Frontiers in Endocrinology, 2019)
Aims It remains controversial to choose the optimal equation to estimate glomerular filtration rate (GFR) in chronic kidney disease (CKD) patients with diabetes. Materials and Methods 215 diabetic CKD patients and 192 non-diabetic CKD patients were enrolled in this study. Iohexol GFR, serum creatinine (SCr) and Cystatin C(CysC) were measured simultaneously for each patient. SCr- and CysC-based estimated GFR (eGFR) were calculated through eight equations, including three CKD-EPI equations, Revised Lund-Malmö study equation (RLM), CAPA equation and three Full Age Spectrum (FAS) equations. Bias, precision and accuracy were compared among eGFR equations with iohexol-GFR serving as measured GFR (mGFR). Independent predictive factors of accuracy were explored using multivariate logistic regression analysis. Results In the diabetic group, CKD-EPISCr-CysC showed the best performance among three CKD-EPI equations (interquartile range of 13.88 ml/min/1.73m2 and 30% accuracy of 72.56%). Compared to CKD-EPISCr-CysC, the other five equations did not significantly improve the performance of GFR estimates. Mostly, eGFR equations were less accurate in diabetic group than in non-diabetic group. Significant differences were found in different mGFR range (P<0.001). The multivariate logistic regression analysis identified that BMI, mGFR and diabetic kidney disease (DKD) status were independent predictors of accuracy of three equations in diabetic group. HbA1c was a predictor of accuracy of CKD-EPISCr and CKD-EPICysC in diabetic group. Conclusions This study showed that eGFR equations were less accurate in diabetic group than in non-diabetic group. CKD-EPIScr-CysC had the best performance among CKD-EPI equations in Chinese diabetic CKD patients. The other five equations did not significantly improve the performance of GFR estimates. BMI, mGFR, DKD status and HbA1c were independent factors associated with accuracy in eGFR equations.